Enhancing workplace digital learning by use of the science of learning. - Kana Okano; Jakub R Kaczmarzyk; John D E Gabrieli (PLoS ONE, 2018)
Digital learning is becoming the most commonly used portal for workplace learning, but its effectiveness is not clearly understood. We studied 99 employees on-site in a large company as they watched an already used and required training video. Employees were randomly assigned to one of four conditions: (1) a baseline condition of watching the video as in current practice; (2) a spontaneous discussion condition in which participants discussed the video with colleagues immediately after the video without any guidelines; (3) a structured discussion condition in which participants discussed the video with colleagues immediately after the video with an instructor guiding discussion topics; and (4) a testing condition in which test questions were interpolated throughout the video. Memory for the content of the video was measured on a recognition memory test completed 20-35 hours after watching the video. Employees who were in the interpolated-testing or structured discussion conditions had significantly superior memory for the video content (26% and 25% better respectively) relative to typical video viewing; spontaneous discussion did not enhance memory for content. These findings demonstrate that interpolated testing and structured discussion enhance information retention in the workplace and point to how learning science may accelerate workplace learning more generally.